The ideologically biased use of Ezra-Nehemiah in a quest for an African theology of reconstruction - Farisani, Elelwani (Old Testament essays, 2002)
This paper examines the impact of an ideologically biased reading of the Biblical text. The paper analyses how certain scholars (Mugambi, Villa-Vicencio and Karamaga) have used the text of Ezra-Nehemiah in a quest for an African theology of reconstruction, without paying particular attention to ideological issues raised by the text. We go on to argue that the de-ideologising of Biblical texts should form part of a critical reading of texts in African scholarship.